Analysis of the implementation of the sisrute application (integrated referral information system) using the end user computing satisfaction (EUCS) method in Lamongan district health facilities - Achmad Nurul Mujahidin (SEAN Institute, 2024)
The government has issued a Letter from the Director General of Health Services on December 10 2018 regarding Applications for the Use of the Integrated Referral System (SISRUTE) to all District/City/Provincial Health Services. The implementation of Sisrute requires an understanding of the use of information systems in the work unit. This research aims to analyze the factors that influence User Satisfaction of the Integrated Referral System Application (SISRUTE) in Lamongan Regency health facilities. The sample in this study were 106 direct users of the SISRUTE application in Lamongan District Health Facilities. This research uses quantitative research with the EUCS method survey research. The results of this study show that there is an influence on satisfaction with using SISRUTE in Lamongan Regency health facilities. Respondents stated that the SISRUTE application was easy to use, and could even be used anytime and anywhere. Some of the reasons respondents rarely use SISRUTE are due to delays in hospital responses and internet connection instability. It can be concluded that perceived ease of use and interest in using it influence the use of the SISRUTE application in Lamongan Regency health facilities.